The Immune Atlas of Human Deciduas With Unexplained Recurrent Pregnancy Loss - Chen, Pengfei; Zhou, Liying; Chen, Jiying; Lu, Ying; Cao, Chaoxia; Lv, Shuangli; Wei, Zhihong; Wang, Liping; Chen, Jiao; Hu, Xinglin; Wu, Zijing; Zhou, Xiaohua; et al. (Frontiers in Immunology, 2021)
Recurrent pregnancy loss (RPL) is a common fertility problem that affects 1-2% of couples all over the world. Despite exciting discoveries regarding the important roles of the decidual natural killer cell (dNK) and regulatory T cell in pregnancy, the immune heterogeneity in patients with unexplained recurrent pregnancy loss (URPL) remain elusive. Here, we profiled the transcriptomes of about 13,953 CD45+ cells from three normal and three URPL deciduas. Based on our data, the cellular composition revealed three major populations of immune cells including dNK cell, T cell, and macrophage, and four minor populations including monocytes, dendritic cell (DC), mast cell, and B cell. Especially, we identified previously unknown variations of immune cells including (i) the decreased proportion of CSF1+CD59+ KIRs-expressing dNK subset in URPL deciduas and (ii) a small subpopulation of ‘activated’ dDCs mainly originated from URPL deciduas. Furthermore, our data revealed that in decidua at early pregnancy, CD8+ T cells exhibited cytotoxic properties. The decidual macrophages expressed high levels of both M1 and M2 feature genes, which made them unique to the traditional M1/M2 classification. Our single-cell data revealed the immune heterogeneity in decidua and the potentially pathogenic immune variations in URPL.